The effects of conventional drugs in the treatment of rheumatoid arthritis on the serum lipids - Karimifar, Mansoor (J Res Med Sci, 2018)
BACKGROUND: Rheumatoid arthritis (RA) is a common chronic autoimmune disorder that leads to damage of human joints. There are various treatment approaches in which different drugs are prescribed which have several alterations in serum lipids. This research aimed to study the effect of RA treatments on the serum lipids. MATERIALS AND METHODS: Two hundred randomly selected patients with RA were randomly assigned to three different groups. The first group of patients was treated with a combination of prednisolone (PRD) and hydroxychloroquine (HCQ). The second group was treated with three drugs including PRD, HCQ, and methotrexate (MTX). The third group was treated with four medications including PRD, HCQ, MTX, and sulfasalazine. Within each group, the lipid factors such as triglyceride (TG), total cholesterol (TC), low-density lipoprotein (LDL), and high-density lipoprotein (HDL), erythrocyte sedimentation rate, and visual analog scale were measured at the beginning of the experiment and 6 months after exposing the treatments. For each group, we also calculated the Disease Activity Score-28 (DAS-28). The analysis of variance revealed that the overall DAS-28 was significantly different among the three groups. RESULTS: In the first group, the level of TG and TC significantly decreased (P = 0.015 and P ≤ 0.001, respectively). In the second group, the level of TG and LDL significantly decreased (P = 0.009). In the third group, the LDL level increased considerably (P < 0.001). The HDL level significantly increased in all three groups (P = 0.012, P = 0.014, and P = 0.028, respectively). CONCLUSION: The treatment PRD + HCQ + MTX was more effective in reducing the LDL level and increasing the HDL level. To reduce the risk of cardiovascular diseases in patients with RA, it is important to prescribe the combination of drugs which leads and normalizes the lipid profile levels.